(untitled) (Itinera, 2022)
The article aims to investigate the relationship between the festive act and the artistic event. What Furio Jesi defines as “peaceful celebration” is likened to the ancient Greek festivities in which the poet shows the unrepeatable repetition of the artistic event, and thus frames it within the community-based realm of friendship. While singing the feast, artists preserve memory and realise an “expropriative” event. This creates an atmosphere in which one dwells in the “unappropriable”, i.e., what one can neither buy nor possess. Although art can enter the market economy and bend to the laws of exhibition, within itself it remains a pulsating festive image that is never entirely reducible to mere commodity. The event of art, in this sense, brings about the unveiling of an excess and turns it into potential. As their role is to trigger and share the celebration, poets are holders of madness understood as the matrix of a festive wisdom, which allows a perception of life as in-depth, dancing rhythm, and which makes itself available to the human community as an opportunity for transformation.